Trend and Rate of Household and Government Contribution to Secondary Education Unit - Sika, James Ochieng (Advances in Social Sciences Research Journal, 2014)
Unit cost of secondary education has continued to rise both direct and indirect jeopardizing access to basic education. The debate has concentrated on whom is carrying the burden of secondary education. The descriptive and causal comparative designs were used in this study. The study sample comprised 85 headteachers’, 765 teachers’, 3349 students and one DEO. The findings of the study indicate that on average households and government contribution to secondary education grew by 3.45 and 4.3 times in absolute terms respectively while under constant terms, the household contribution was 23 times and 25 times for day and boarding schools respectively. The government contribution was 15 times over the same time period. It was concluded that the household carry heavy responsibility compared to the government and hence acquisition of secondary education is still a problem to most household.